APLIKASI PENCARIAN RUTE ANGKUTAN UMUM DI BANDAR LAMPUNG BERBASIS MOBILE ANDROID - Deby Ariyandi; Didik Kurniawan; Astria Hijriani (Jurnal Komputasi, 2016)
Nowadays the development of information technology is growing rapidly not even be stopped. Such as the communication problems, which recently seemed there is no distance anymore, everything feels close, it is all because of technology. Along with the development of science and technology, emerging technology development is a GPS (Global Positioning System). In this study, researchers design and build android-based application to find out public transport route in Bandar Lampung called Balam Trans utilizing GIS technology in it. This application allows you to search route of the city transportation (Angkot) and Bus Rapid Transit (BRT) in the city of Bandar Lampung, so users no longer have difficulty in finding public transport to get to their destination location, especially for migrants in the city of Bandar Lampung. Additionally, this application can display information about public transportation and BRT route so as to broaden the users knowledge. This application was developed using Dijkstra's Algorithm for finding the shortest route. The conclusion of this study is the application Balam Trans successfully constructed and useful for every user who has used this Balam Trans applications, proved by questionnaire application testing achieves good.Â Keywords : Balam Trans, Public Transportation, Angkot, BRT, Route, Dijkstra's algorithm, Play Store, Android, Smartphone, Bandar Lampung.